Innovations in Healthcare Big Data Engineering: From Clinical Decision Support to Federated Learning - Jagan Mohana Rao Bonthu, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article review explores the transformative impact of big data engineering and analytics in healthcare, from clinical decision support systems to federated learning implementations. The article examines how artificial intelligence and machine learning technologies revolutionize healthcare delivery through enhanced diagnostic capabilities, real-time monitoring solutions, and precision medicine approaches. It shows the integration of advanced analytics in drug discovery and development processes, highlighting how these technologies accelerate research and improve treatment outcomes. The article also addresses critical security and privacy aspects in healthcare data management, particularly focusing on blockchain technology and federated learning applications. Through analysis of various technological implementations and their clinical impacts, this article demonstrates how big data engineering fundamentally reshapes healthcare delivery, enabling more personalized, efficient, and secure patient care while simultaneously addressing challenges in data privacy, system interoperability, and regulatory compliance.
Keywords: Healthcare Analytics; Clinical Decision Support Systems; Precision Medicine; Federated Learning; Blockchain Technology